The Influence of Cognitive Motor Training on Functional Outcomes in Individuals with Chronic Ankle Sprain: A Systematic Review Protocol - Selvaganapathy, Karthikeyan; M, Kamalakannan; Rajappan, Roshini; Abudaheer K, Syed (Journal of Neonatal Surgery, 2025)
Background: A very common ailment that inhibits both functionality and balance is Chronic Ankle Sprain (CAS). One potential way to treat such condition seems to be cognitive-motor training (CMT) that combines motor as well as cognitive tasks during rehabilitation. Objectives: This protocol described the proposed systematic review that aims to evaluate the effectiveness of CMT in improving proprioception, functional recovery, and reducing recurrence rates in CAS patients. Methods: An effective systematic review will be following PRISMA guidelines. These will be the database sources searched: PubMed, Scopus, Web of Science, and the Cochrane Library. Studies subjected to eligibility criteria were randomized controlled trials and quasi-experimental studies concerning CAS, which included CMT interventions. Data extraction and analysis will include quantitative and narrative synthesis as appropriate. Conclusion: Findings would shed light on the role of CMT in CAS management and provide implications for future rehabilitation practices.